2009
DOI: 10.1891/0886-6708.24.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Impaired and Incapacitated Rape Victims: Assault Characteristics and Post-Assault Experiences

Abstract: Alcohol is the most common "rape drug," with up to two-thirds of victims consuming alcohol prior to the assault. Surprisingly, little research has examined the assault and postassault experiences of victims who were impaired or incapacitated as a result of substance use, including alcohol, during a rape. Thus, the current study evaluated the assault and postassault experiences of a sample of 340 nonimpaired, impaired, and incapacitated college rape victims. Results supported that these three groups differed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
148
8
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 40 publications
20
148
8
2
Order By: Relevance
“…Second, our assessment strategy did not distinguish between incapacitation due to voluntary consumption of alcohol or other drugs and nonconsensual use of date rape or predator drugs such as Rohypnol (Kilpatrick et al, 2007;Testa & Livingston, 2009). Prior research indicates that incapacitation because of voluntary consumption is more common (Lawyer et al, 2010;Littleton et al, 2009), but our data do not allow us to distinguish these two forms. Third, the baseline assessment took place in the first few weeks of the semester, referring back to the month of August.…”
Section: Strengths and Limitations Of The Researchcontrasting
confidence: 58%
See 1 more Smart Citation
“…Second, our assessment strategy did not distinguish between incapacitation due to voluntary consumption of alcohol or other drugs and nonconsensual use of date rape or predator drugs such as Rohypnol (Kilpatrick et al, 2007;Testa & Livingston, 2009). Prior research indicates that incapacitation because of voluntary consumption is more common (Lawyer et al, 2010;Littleton et al, 2009), but our data do not allow us to distinguish these two forms. Third, the baseline assessment took place in the first few weeks of the semester, referring back to the month of August.…”
Section: Strengths and Limitations Of The Researchcontrasting
confidence: 58%
“…Sexual assaults that follow alcohol use (e.g., IR) are associated with significant emotional distress (Brown et al, 2009) and can lead female victims to blame themselves and to feel stigmatized by peers (Littleton et al, 2009).…”
mentioning
confidence: 99%
“…In contrast, the vast majority of rape victims are at least acquainted with their assailant and only a very small percentage involve the use of severe violence (e.g., McMullin and White 2006). In addition, while a sizable percentage of rapes occur when the victim is intoxicated or impaired due to voluntary ingestion of alcohol (e.g., Littleton et al 2009b;Zinzow et al 2010), this possibility is mentioned much less frequently in individuals' rape scripts, and when it is, the focus is often on the perpetrator drugging the victim by slipping something in her drink (Littleton et al 2009c). Finally, individuals' rape scripts rarely involve a perpetrator or victim who had previously engaged in consensual sexual behavior or a rape that started out as a consensual encounter (e.g., Littleton et al 2007a;Littleton et al 2009c;Ryan 1988).…”
Section: Rape Scriptsmentioning
confidence: 99%
“…Of the few studies that investigate intoxication in various assault-types in relation to mental health, one found that women who had not used alcohol prior to sexual assault showed more intrusion symptoms, but a quicker reduction in these symptoms, than women who had used alcohol prior to the assault (Kaysen et al, 2010). Another study found that rape victims who were impeded or incapacitated by alcohol during the event exhibited more hazardous drinking post-assault than non-impeded victims, although the groups did not differ in terms of depression and anxiety symptoms (Littleton, Grills-Taquechel, & Axsom, 2009). Myths about sexual assault may lead social networks to respond differentially to intoxicated and non-intoxicated sexual assault victims, but little is known about whether these groups of victims differ in terms of social functioning.…”
Section: Introductionmentioning
confidence: 99%